Characterization of the rho genes of Neisseria gonorrhoeae and Salmonella typhimurium. - Miloso, M (1993)
We have cloned and sequenced the genomic regions encompassing the rho genes of Neisseria gonorrhoeae and Salmonella typhimurium. Rho factor of S. typhimurium has only three amino acid differences with respect to the Escherichia coli homolog. Northern (RNA) blots and primer extension experiments were used to characterize the N. gonorrhoeae rho transcript and to identify the transcription initiation and termination elements of this cistron. The function of the Rho factor of N. gonorrhoeae was investigated by complementation assays of rho mutants of E. coli and S. typhimurium and by in vivo transcription assays in polar mutants of S. typhimurium.